Intraoperative Computed Tomography Scan for Orbital Fracture Reconstruction. Issue 7 (October 2019) - Nazimi, Abd Jabar; Khoo, Soo Ching; Nabil, Syed; Nordin, Rifqah; Lan, Tan Huann; Rajandram, Rama Krsna; Rajaran, Jothi Raamahlingam
Abstract : Abstract: Orbital fractures pose specific challenge in its surgical management. One of the greatest challenges is to obtain satisfactory reconstruction by correct positioning of orbital implant. Intraoperative computed tomography (CT) scan may facilitate this procedure. The aim of this study was to describe the early use of intraoperative CT in orbital fractures repair in our center. The authors assessed the revision types and rates that have occurred with this technique. With the use of pre-surgical planning, optical intraoperative navigation, and intraoperative CT, the impact of intraoperative CT on the management of 5 cases involving a total number of 14 orbital wall fractures were described. There were 6 pure orbital blowout wall fractures reconstructed, involving both medial and inferior wall of the orbit fracturing the transition zone and 8 impure orbital wall fractures in orbitozygomaticomaxillary complex fracture. 4 patients underwent primary and 1 had delayed orbital reconstruction. Intraoperative CT resulted in intraoperative orbital implant revision, following final navigation planning position, in 40% (2/5) of patients or 14% (2/14) of the fractures. In revised cases, both implant repositioning was conducted at posterior ledge of orbit. Intraoperative CT confirmed true to original reconstruction of medial wall, inferior wall and transition zone of the orbit. Two selected cases were illustrated. In conclusion, intraoperative CT allows real-time assessment of fracture reduction and immediate orbital implant revision, especially at posterior ledge. As a result, no postoperative imaging was indicated in any of the patients. Long-term follow-ups for orbital fracture patients managed with intraoperative CT is suggested. Abstract : Supplemental Digital Content is available in the text